Drug governs the morphology of polyalkylated block copolymer aggregates. Issue 7 (9th December 2016) - Le Dévédec, F.; Her, S.; Vogtt, K.; Won, A.; Li, X.; Beaucage, G.; Yip, C.; Allen, C.
Abstract : Polyalkylated copolymers based on mPEG- b -(AGE-C6, 12 or 18 )25 have been used to formulate clinically relevant concentrations of doxorubicin (DOX) and the impact of drug incorporation on copolymer aggregation behaviour was examined. Abstract : Polyalkylated copolymers based on mPEG- b -(AGE-C6, 12 or 18 )25 have been used to formulate clinically relevant concentrations of doxorubicin (DOX) and the impact of drug incorporation on copolymer aggregation behaviour was examined. The copolymer aggregates were analyzed by various microscopy techniques (TEM, cryo-TEM and AFM) and scattering methods (SANS, DLS). In the absence of the drug, the copolymers formed largely non-spherical aggregates ( i.e. cylinders, vesicles). Drug incorporation during copolymer aggregate formation directed the formation of only spherical aggregates. As well, the nature of the core-forming block was found to influence drug release and cytotoxicity of the formulations.